1998
DOI: 10.1002/1529-0131(199809)41:9<1652::aid-art17>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of splenic B1a cells with potent antigen-presenting capability in NZM2410 lupus-prone mice

Abstract: Objective. In order to shed light on the role of splenic B1 cells in disease pathogenesis in lupus-prone mice, this study was undertaken to determine how efficiently these cells can serve as antigen-presenting cells (APC) and to ascertain which mnrine lupus susceptibility loci dictate the expansion of these cells.Methods. Spleens and peritoneal cavities (PerC) of NZM2410 lupus-prone mice, as well as of control B6 and New Zealand white mice, were examined for the prevalence, surface phenotype, and possible anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 65 publications
2
77
0
Order By: Relevance
“…In patients with SLE, the balance between these interactions would be shifted in the direction of autoimmunity either due to intrinsic B cell defects, abnormal T cell responses or both [123,124] and MZ B cells stimulated by T cells could enter the GC reaction [125]. Of particular interest in this respect is the expansion of αβ DN T cells observed in murine and human lupus and in patients with the autoimmune lymphoproliferative syndrome (ALPS), who have a very high incidence of autoantibody-mediated cytopenias [119,126,127,128,129,130,131].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with SLE, the balance between these interactions would be shifted in the direction of autoimmunity either due to intrinsic B cell defects, abnormal T cell responses or both [123,124] and MZ B cells stimulated by T cells could enter the GC reaction [125]. Of particular interest in this respect is the expansion of αβ DN T cells observed in murine and human lupus and in patients with the autoimmune lymphoproliferative syndrome (ALPS), who have a very high incidence of autoantibody-mediated cytopenias [119,126,127,128,129,130,131].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, congenic dissection studies have also shed light on the respective roles of these loci in disease pathogenesis. [21][22][23][24][25][26][27] The (SWR × NZB)F1 (or SNF1) hybrid model is another strain which develops lupus nephritis that is clinically very similar (in onset, severity, female bias, and pathology) to the BWF1 disease. Studies in this model have clearly demonstrated the relative contributions of antigen-specific, and antigen non-specific modalities of T cell: B cell cross-talk in orchestrating disease, as reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, expanded B1a cells constitute a prominent feature in these mice, particularly during maturation (28,29). To ascertain if IFN-I had any effect on the occurrence of these B cells, B6 and B6.Sle2 mice treated with IFN-I, anti-IFN-I antibodies, or placebo were examined for the relative frequencies of peritoneal and splenic B1a, B1b, and B2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The NZM2410 Sle2 interval was inherited in part from NZW, and in part from NZB. The immunologic phenotypes of the B6.Sle2 congenic strain have previously been reported (26)(27)(28)(29). B6.Sle1 NZM2410/NZM2410 (simply referred to as B6.Sle1) mice are congenic homozygotes for the 95% confidence interval flanking Sle1, derived from the NZM2410 strain, as previously described (27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation